Daily Treatment Planning with an On-Line Shared Computer System - Gotcher, S. B.; Caerick, J.; Vallbona, C.; Spencer, W. A.; Carter, R. E.; Cornell, S. (Methods of Information in Medicine, 1969)
For six months the treatment plans of an average of 30 patients have been scheduled through the use of remote terminals on-line to a computer. Updated schedules of the treatment plan for each patient, department, and nursing unit have been produced daily and are used by the physicians, departmental directors, allied health professionals, and supportive personnel. A preliminary assessment of the usefulness of the system has indicated that it has: (a) assisted personnel in coordination and implementation of the required treatment plan, (b) provided an effective method of analysis of the total care program, (c) improved utilization of space and personnel, (d) helped the patients gain a better understanding of their care program, and (e) provided an excellent teaching tool and valuable resources for research and cost analysis.